2020
DOI: 10.24953/turkjped.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of different doses of ursodeoxycholic acid on neonatal jaundice

Abstract: Background. Icterus tends to be one of the most prevalent causes of neonatal hospitalization. The present study aimed to evaluate the effects of the different doses of ursodeoxycholic acid (UDCA) on neonatal jaundice. Method. In this study, 120 newborns who were hospitalized for phototherapy were randomly assigned. Group A received phototherapy and UDCA 5 mg/kg/dose every 12 hours orally, group B patients were treated with phototherapy and UDCA 7.5 mg/kg/dose every 12 hours orally. Group C received photot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…We did not perform any subgroup analysis based on the different doses as it was not preplanned. We observed that the studies with a higher dose [ 19 , 21 ] showed similar results compared to the studies using smaller doses of UDCA. The optimal dose with the best benefit/harm ratio remains to be determined as majority of the studies included in this meta-analysis did not report any adverse effects.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…We did not perform any subgroup analysis based on the different doses as it was not preplanned. We observed that the studies with a higher dose [ 19 , 21 ] showed similar results compared to the studies using smaller doses of UDCA. The optimal dose with the best benefit/harm ratio remains to be determined as majority of the studies included in this meta-analysis did not report any adverse effects.…”
Section: Discussionsupporting
confidence: 57%
“…The limitations of this review are largely those of the primary studies. As four of the studies were not placebo-controlled [ 17 – 21 ] and one of these did not comment on the blinding at all [ 17 ], the results presented here are vulnerable to bias. Furthermore, only one of the included studies reported adverse outcomes [ 22 ], and none of the studies reported rehospitalization rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there is limited strong evidence about the use of pharmacotherapy such as clofibrate, human albumin, intravenous immunoglobulin, herbal therapy, ursodeoxycholic acid, and phenobarbital treatment in neonatal jaundice. [ 12 18 19 20 21 ] Clofibrate is an aryloxyisobutyric acid derivative used in the treatment of hypertriglyceridemia and dyslipidemia. [ 13 ] However, previous studies showed that clofibrate is effective in the treatment of neonatal jaundice.…”
Section: Introductionmentioning
confidence: 99%